Tuning Reactivity and Selectivity for Olefin Oxidation through Local O Bonding on Au - Min, Byoung Koun; Deng, Xingyi; Li, Xiaoying; Friend, Cynthia M.; Alemozafar, Ali Reza (WILEY-V C H VERLAG GMBH, 2009)
The reactivity and selectivity for the oxidation of propene and acrolein on oxidized Au nanoparticles on Au(111) depend on the local bonding, the particle size, and the degree of order. The local bonding of O and the particle size distribution and order are controlled by the rate and temperature for oxygen deposition using ozone, which forms O-containing gold particles on the surface. On small, disordered particles, oxygen is bound in sites with local threefold coordination, based on measured vibrational energies. The O on these small disordered nanoclusters, formed by O-3 decomposition on Au(111) at 200 K, is highly reactive and yields partial oxidation products of propene, for example, acrolein and acrylic acid. In contrast, atomic oxygen present in ordered 2D islands formed at 400 K is relatively unreactive and only produces CO2 and H2O. All pathways involve initial C-H activation. These results indicate that local bonding of O is an important factor to consider in understanding the effect of particle size in gold-based catalysis involving hydrocarbons.
Keywords: SCANNING-TUNNELING-MICROSCOPY; OXYGEN-COVERED AU(111); ATOMIC OXYGEN; HYDROGEN-PEROXIDE; LOW-TEMPERATURE; GOLD CATALYSTS; METAL-SURFACES; CO OXIDATION; ADSORPTION; NANOPARTICLES